Black swan events and safe havens: The role of gold in globally integrated emerging markets. (May 2017) - Bekiros, Stelios; Boubaker, Sabri; Nguyen, Duc Khuong; Uddin, Gazi Salah
Highlights: We examine hedging and diversification roles of gold for the BRICS markets. We use wavelet and GARCH-based copula methodologies. There is evidence of time-scale co-evolvement and asymmetric dependence. Gold is a diversifier in both normal and bear markets for BRICS stocks. Data do not support evidence that gold is a hedge and a safe haven. Abstract: There is evidence to suggest that gold acts as both a hedge and a safe haven for equity markets over recent years, and particularly during crises periods. Our work extends the recent literature on hedging and diversification roles of gold by analyzing its interaction with the stock markets of the leading emerging economies, the BRICS. While they generally exhibit a high growth rate, these economies still experience a pronounced vulnerability to external shocks, particularly to commodity price fluctuations. Using a multi-scale wavelet approach and a GARCH-based copula methodology, we mainly show evidence of: ( i ) the time-scale co-evolvement patterns between BRICS stock markets and gold market, with some profound regions of concentrated extreme variations; and ( ii ) a strong time-varying asymmetric dependence structure between those markets. These findings are essential for risk diversification and portfolio hedging strategies among the investigated markets.